L’édification d’un « parc imaginaire » des Cévennes - Karine-Larissa Basset; Jean-Noël Pelen (Territoire en Mouvement)
From the 18th century onwards, through a broad range of text forms (written and oral, fictional and realist, academic and popular...), literary work has elaborated a set of shared references and hallmarks that constitute “the Identity of the Cévennes.” In the 1950s, the idea of a park emerged locally, materializing in 1970, drawing from this literary matrix elements developed into heritage (landscapes of terraces and chestnut trees, “Cévennes” oral memory, Protestantism, virtues of resistance and openness, etc.). This transformation into heritage fuels the reference to a model of development which represents an alternative to mass tourism, between recurrent nostalgia for a mythified countryside and promotion of traditional activities (agriculture, pastoralism, and crafts), following the precepts of “sustainable conservation.” The capacity of the Cévennes “imaginary park” (A. Chamson) to become a resource for land planning showed limits in the early 2000s, when the project to inscribe “the Cévennes cultural landscape” on the list of mixed sites of UNESCO world heritage was rejected by international experts, who insisted on the creation of a consensual heritage site of “universal” value that does not fit the local way of defining the identity of places. Another literary heritage in the Cévennes, associated with Anglo-Saxon bioregionalism, was mostly ignored, although it strives to combine the identity of the place with an eco-centered approach in a single project for the area.